A deletion of FGFR2 creating a chimeric IIIb/IIIc exon in a child with Apert syndrome. - Fenwick, A; Bowdin, S; Klatt, R; Wilkie, A (BioMed Central, 2011)
BACKGROUND: Signalling by fibroblast growth factor receptor type 2 (FGFR2) normally involves a tissue-specific alternative splice choice between two exons (IIIb and IIIc), which generates two receptor isoforms (FGFR2b and FGFR2c respectively) with differing repertoires of FGF-binding specificity. Here we describe a unique chimeric IIIb/c exon in a patient with Apert syndrome, generated by a non-allelic homologous recombination event. CASE PRESENTATION: We present a child with Apert syndrome in whom routine genetic testing had excluded the FGFR2 missense mutations commonly associated with this disorder. The patient was found to harbour a heterozygous 1372 bp deletion between FGFR2 exons IIIb and IIIc, apparently originating from recombination between 13 bp of identical DNA sequence present in both exons. The rearrangement was not present in the unaffected parents. CONCLUSIONS: Based on the known pathogenesis of Apert syndrome, the chimeric FGFR2 protein is predicted to act in a dominant gain-of-function manner. This is likely to result from its expression in mesenchymal tissues, where retention of most of the residues essential for FGFR2b binding activity would result in autocrine activation. This report adds to the repertoire of rare cases of Apert syndrome for which a pathogenesis based on atypical FGFR2 rearrangements can be demonstrated.